2013
DOI: 10.1074/jbc.m112.393629
|View full text |Cite
|
Sign up to set email alerts
|

Murine Hyaluronidase 2 Deficiency Results in Extracellular Hyaluronan Accumulation and Severe Cardiopulmonary Dysfunction

Abstract: Background:The role of hyaluronidase 2 in hyaluronan degradation and cardiopulmonary function is largely uncharacterized. Results: Hyaluronidase 2-deficient mice accumulate extracellular hyaluronan, leading to defective cardiopulmonary function. Conclusion: Hyaluronidase 2 is essential for hyaluronan degradation and normal heart and lung health. Significance: Our studies suggest that hyaluronidase 2 deficiency should be considered as a contributor to cardiac pathologies in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 34 publications
5
77
1
Order By: Relevance
“…The expression of extracellular matrix (ECM)-degrading proteases [ctsba, ctssb.1 (ctss2.1), mmp9] and hyaluronidase 2 (hyal2), which degrades hyaluronan (Chowdhury et al, 2013), was increased in Notch-diminished hearts (Fig. 5A).…”
Section: Decreased Notch Signalling Affects Endothelial Cardiovasculmentioning
confidence: 99%
“…The expression of extracellular matrix (ECM)-degrading proteases [ctsba, ctssb.1 (ctss2.1), mmp9] and hyaluronidase 2 (hyal2), which degrades hyaluronan (Chowdhury et al, 2013), was increased in Notch-diminished hearts (Fig. 5A).…”
Section: Decreased Notch Signalling Affects Endothelial Cardiovasculmentioning
confidence: 99%
“…Hyal2 deficient mice displayed a significant increase in plasma HA and increased HA in the interstitial extracellular matrix of atrial cardiomyocytes [39, 40], suggesting that HYAL2 is essential for the breakdown of extracellular HA. Hyal2 deficient mice showed severe cardiopulmonary dysfunction [40].…”
Section: Introductionmentioning
confidence: 99%
“…Hyal2 deficient mice showed severe cardiopulmonary dysfunction [40]. Platelet-derived hyaluronidase 2 cleaves HA into fragments that trigger monocyte-mediated production of pro-inflammatory cytokines [41].…”
Section: Introductionmentioning
confidence: 99%
“…It was the first GAG discovered in 1934 by Karl Meyer and John W. Palmer 37 and, therefore, most comprehensively described in the heart. [38][39][40][41][42][43][44][45][46][47][48][49][50] The expression of hyaluronan is upregulated in experimental models of myocardial infarction (MI), 50 myocarditis, 51 and cardiac hypertrophy. 43,49 In 1985, West et al 52 demonstrated that oligosaccharides derived from high-molecular-weight hyaluronan can have very distinct functions compared with the large hyaluronan variants.…”
Section: Hyaluronan and Heparinmentioning
confidence: 99%